Medawar’s PostEra: Galectins Emerged as Key Players During Fetal-Maternal Glycoimmune Adaptation - Menkhorst, Ellen; Than, Nandor Gabor; Jeschke, Udo; Barrientos, Gabriela; Szereday, Laszlo; Dveksler, Gabriela; Blois, Sandra M. (Frontiers in Immunology, 2021)
Lectin-glycan interactions, in particular those mediated by the galectin family, regulate many processes required for a successful pregnancy. Over the past decades, increasing evidence gathered from in vitro and in vivo experiments indicate that members of the galectin family specifically bind to both intracellular and membrane bound carbohydrate ligands regulating angiogenesis, immune-cell adaptations required to tolerate the fetal semi-allograft and mammalian embryogenesis. Therefore, galectins play important roles in fetal development and placentation contributing to maternal and fetal health. This review discusses the expression and role of galectins during the course of pregnancy, with an emphasis on maternal immune adaptions and galectin-glycan interactions uncovered in the recent years. In addition, we summarize the galectin fingerprints associated with pathological gestation with particular focus on preeclampsia.